A simple microabrasion technique as aesthetic approach on fluorosis of anterior teeth - Maulidia Indah SARI; Irmaleny SATIFIL (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Dentistry treatment is not only focused on restoring the function of mastication but also onthe aesthetic problem. Fluorosis is one of the aesthetic problems caused by excessive fluoride intakeduring email formation and produced color changes on the surface of the email. Fluorosis was notaffected by the aesthetics but also influenced the confidence of the patient. The Microabrasion techniqueis an option for fluorosis because it is conservative treatment with good results. A 20-year-old womanwho came to the Dental Conservation clinic complained that she wants to remove the brown color andwhite spots seen on the front teeth, which significantly interfere with her appearance. Based on clinicalexamination, many cavities were found in the back teeth of the upper and lower jaw. The results of thehistory and clinical study revealed that the patient had fluorosis in her teeth. Microabrasion was carriedout using Opalustre (ultradent). This material was applied to the tooth surface and rubbed using anapplicator (opal bristle) for 60 seconds. Then applied fluoride gel paste with finishing cup opal.Treatment results showed changes in tooth color, brown and white patches disappeared. Microabrasionis the first choice for aesthetic treatment in fluorosis and has shown satisfying results to restore thepatient's aesthetics problem. KEYWORDS: Fluorosis, microabrasion technique